1998
DOI: 10.1302/0301-620x.80b4.0800611
|View full text |Cite
|
Sign up to set email alerts
|

Cement as a risk factor for deep-vein thrombosis

Abstract: A total of 110 total knee replacements (TKRs) was randomised to receive either a cemented or an uncemented prosthesis. Postoperative venography at five to seven days was used to compare the prevalence, site and size of deep-vein thrombosis (DVT). We also compared the findings with those of postoperative venography in a group of patients with cemented total hip replacements (THRs).The total prevalence of DVT was significantly greater after uncemented (81%) than after cemented TKR (55%). Both knee groups had a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Our study determined cement fixation to not be a significant risk factor for VTE compared to patients with cementless prostheses. These findings correlate with several studies that have compared cemented to cementless patients undergoing TKA [ 11 , 12 , [19] , [20] , [21] ]. The large meta-analysis of Liu et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study determined cement fixation to not be a significant risk factor for VTE compared to patients with cementless prostheses. These findings correlate with several studies that have compared cemented to cementless patients undergoing TKA [ 11 , 12 , [19] , [20] , [21] ]. The large meta-analysis of Liu et al.…”
Section: Discussionsupporting
confidence: 89%
“…involving 26 studies, which compared the rates of DVT between cemented and cementless TKA cases, reported no significant difference between the 2 groups [ 19 ]. Additionally, the RCT by Clarke et al., which randomized patients to receive either a cemented or cementless prosthesis, demonstrated no significant increase in the VTE incidence in the cemented group [ 20 ]. While several studies have identified cement as a significant risk factor for VTE [ 11 , 12 ], our findings correlate with other reports that the use of cement does not increase the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review by Hitos et al, cemented TKA was associated with a rate of deep venous thrombosis (DVT) that was statistically significantly higher than cementless TKA 541 . An RCT with venographic endpoints by Clark et al, comparing cementless TKA, cemented TKA, and cemented THA found an increased length of the thrombus with cemented TKA but no difference in incidence of DVT among the three groups 542 . Two prospective cohort studies that were underpowered found no effect of cement vs. cementless fixation on DVT rate following TKA 543,544 .…”
Section: - Does the Use Of Pmma Cement During Orthopaedic Procedures ...mentioning
confidence: 99%
“…Clarke et al studied the bone cement as a risk factor for DVT, comparing three sets of patients undergoing a cemented or uncemented total knee replacement (TKR) or a cemented total hip replacement (THR) [11]. They found that uncemented prostheses were associated with a greater prevalence of DVT at 5 to 7 days than cemented prostheses, and both knee groups had a significantly higher prevalence of DVT than the cemented THR group.…”
Section: Discussionmentioning
confidence: 99%